Dual Bmp-negative feedback loops modulate function of both AER and ZPA to buffer and constrain postaxial digit number - Rashmi Patel; Susan Mackem (Proceedings of the National Academy of Sciences, 2025)
Several lines of evidence indicate that posterior (postaxial) digit number in tetrapod vertebrates is constrained to the pentadactyl state by interactions between the two major signaling centers that organize digit pattern and growth, the Sonic hedgehog (Shh)-expressing Zone of Polarizing Activity (ZPA) and the Fgf-expressing Apical Ectodermal Ridge (AER) ectoderm. Negative short-range effects of Shh on the immediately overlying AER limit its posterior extent and function, either by direct Shh signaling or with Bmps playing a key role. How this strong inhibitory effect is counterbalanced to maintain pentadactyly in many vertebrate species remains less clear. In this study, we used genetic approaches in mice to reevaluate the mechanism by which Shh signaling modulates AER function and demonstrate that this occurs via Shh-target Bmps that act as a relay signal, rather than by direct Shh action. Furthermore, we show that Shh-induced Bmps also act directly on the ZPA, in a negative feedback loop, to down-regulate Shh expression and ZPA extent. We provide evidence that these dual Bmp-driven negative feedback loops robustly balance total Bmp levels to constrain postaxial digit number.